Exploring high school students’ attitudes towards digital game-based learning: A perspective from Indonesia - Irwanto, Irwanto; Cahyana, Ucu; Ayuni, Ni Putu Sri; Wijayako, Rudi Suhartono (Journal of Education and e-Learning Research, 2024)
Students’ attitudes towards Digital Game-Based Learning (DGBL) in developing countries such as Indonesia are rarely investigated despite the fact that digital games are being used in secondary education increasingly. This research aims to explore students’ attitudes towards DGBL in chemistry. We used a quantitative study method using a self-reported survey questionnaire. The study included 480 high school students (203 males and 277 females) from various public and private high schools in Indonesia. The present study employed a cross-sectional survey design to collect data in July and August 2023. The DGBL attitude scale was adapted to evaluate students’ attitudes. The questionnaire comprised 22 items assessing students’ attitudes towards digital game-based learning. The data obtained were analyzed using descriptive statistics as well as t-tests and a one-way Analysis of Variance (ANOVA). As a result, students expressed a slightly positive attitude towards digital games in chemistry learning particularly for learning opportunities. The results also showed that there was a significant gap in students’ attitudes with regard to gender and the daily duration of smartphone use. However, there was no significant gap regarding students’ attitudes towards digital game-based learning. The findings provide valuable insights for game designers and teachers to design and implement educational games that meet student needs and expectations in order to improve learning outcomes. The results are also useful for educators and educational researchers on how demographic factors influence students’ DGBL attitudes in chemistry education in developing countries such as Indonesia.